Smart investments by smart money: Evidence from seasoned equity offerings - Gibson, Scott; Safieddine, Assem; Sonti, Ramana (Journal of Financial Economics, 2004)
We document that seasoned equity issuers experiencing the greatest increase in institutional investment around the offer date outperformed their benchmark portfolios in the year following the issue by a statistically and economically significant margin relative to those experiencing the greatest decrease. No such relationship exists for a control sample of matched non-issuers. Issuers with the greatest institutional investment are also found to have the highest ratio of sell-side analyst upgrades less downgrades to total forecasts in the two quarters following the issue. Again, no such relationship is found for matched non-issuers. We interpret our results as evidence that institutions are able to identify above-average seasoned equity offering SEO firms at the time of equity issuance and increase their holdings in these potential outperformers.